2003
DOI: 10.1359/jbmr.2003.18.5.900
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk After Bilateral Oophorectomy in Elderly Women

Abstract: Elderly women with the lowest serum estrogen levels are at the greatest risk of bone loss and fractures, but it is controversial whether the ovaries contribute to estrogen production after menopause, and therefore, whether bilateral oophorectomy in postmenopausal women might have adverse skeletal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
4
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 60 publications
0
57
4
1
Order By: Relevance
“…The latter is of particular concern since bilateral oophorectomy is associated with an increased risk of fractures, although the greatest risk appears to be for those with oophorectomy prior to age 45 [24,25]. An increased risk of heart disease and stroke, as well as excess mortality, has been associated with oophorectomy prior to age 45 in the general population, most apparent in those who did not take HRT after oophorectomy [7,19,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is of particular concern since bilateral oophorectomy is associated with an increased risk of fractures, although the greatest risk appears to be for those with oophorectomy prior to age 45 [24,25]. An increased risk of heart disease and stroke, as well as excess mortality, has been associated with oophorectomy prior to age 45 in the general population, most apparent in those who did not take HRT after oophorectomy [7,19,[26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that osteoporotic fracture risk was elevated 1.5-fold among 340 women who underwent bilateral oophorectomy following a natural menopause (1). To the extent that the ovaries contribute to postmenopausal estrogen production via extragonadal conversion of ovarian androgens to estrogen (2), oophorectomy might have exacerbated bone loss in these women and increased their risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Bones that are affected by osteoporosis can fracture with relatively minor injury that normally would not cause a bone to fracture. The Fracture can be either in the form of cracking or collapsing [2] …”
Section: What Is Osteoporosismentioning
confidence: 99%
“…Currently, we compute the posterior probability P(X|Yes) and P(X|No) by using equation (2).The Bayes Error Rate was compute as in equation (4). Figure( 24) show the Osteoporosis Naïve Bayes classification, for each patent.…”
Section: Fig 23: Form Of the Prior Probabilitymentioning
confidence: 99%